Hubungan Self Efficacy dengan Quarter Life Crisis pada Mahasiswa Semester Akhir: Self Efficacy as a Predictor of Quarter-Life Crisis in Final Year University Student - Puspa Jelita; Anik Suwarni; Indriyati (Jurnal Keperawatan Berbudaya Sehat, 2026)
Quarter life crisis is a phase commonly experienced by individuals in early adulthood, including university students, characterized by anxiety, confusion, and uncertainty in determining life direction. One factor that is thought to influence this condition is self efficacy. This study aimed to determine the relationship between self efficacy and quarter life crisis among seventh-semester students of the Faculty of Science, Technology, and Health at Sahid Surakarta University. This study employed a quantitative correlational approach with a cross-sectional design. The population consisted of 104 students, with 83 respondents selected as the sample using a stratified random sampling technique. Data were collected using questionnaires and analyzed using Kendall’s Tau test. The results showed that most respondents had high self-efficacy (67.5%) and low levels of quarter life crisis (59.0%). The analysis revealed a significant relationship between self-efficacy and quarter life crisis, where higher self-efficacy was associated with lower levels of quarter life crisis, indicated by a p-value of 0.000 (p < 0.05) and a correlation coefficient of -0.788. The study concluded that there is a negative relationship between self-efficacy and quarter life crisis. The higher the self-efficacy, the lower the level of quarter life crisis among students.